Synthesis and characterization of sprayed LiNiVO4 thin films: New application areas. (May 2021) - El-Bana, M.S.; AlKhalifah, M.S.; El Radaf, I.M.; Labidi, A.
Highlights: LiNiVO4 films have been deposited using the low cost spray pyrolysis technique. Films can be utilized as a promising candidate in optoelectrical devices. LiNiVO4 films sprayed on glass substrates show promising sensitivity towards ethanol. Sensing response versus working temperature reveals an optimal temperature at 200 °C. Ethanol sensing response confirms the LiNiVO4 p-type semiconductor character. Abstract: Quaternary LiNiVO4 is a superb cathode material in lithium-ion batteries. There is, however, a lack of knowledge about the possibility of using it in other application areas. Therefore, the researchers attempted to fill in the knowledge gap regards to the possibilities of using it in other technologies. LiNiVO4 thin films were sprayed using the spray pyrolysis technique. The investigated films have revealed interesting optical and optoelectrical properties. Besides, ethanol-sensing properties have been examined via DC measurements. The change in working temperatures is found to affect the degree of material's sensitivity. Furthermore, the effect of film thickness on a layer's sensibility has been tested. This has enabled us to explain the mechanisms of ethanol vapor interaction. In light of the obtained results, we could expect the rising of novel properties of these quaternary films. This would pave the way for using such interesting material in optoelectronic devices and/or gas sensors devices.